Pasta : the spirit and craft of Italy's greatest food, with recipes - Robbins, Missy; Baiocchi, Talia (Ten Speed Press, 2021)
In this hard-working manual for home cooks who aspire to master the art of pasta cooking, the James Beard Award-winning chef/owner of the acclaimed Lilia and Misi in Brooklyn presents recipes for 40 handmade pasta shapes and 100 Italian American, regional Italian and modern dishes.